Analytical Differences in Intraoperative Parathyroid Hormone Assays. (1st March 2019) - Leung, Edward K Y; Lee, Christine C; Angelos, Peter; Kaplan, Edwin L; Grogan, Raymon H; Sarracino, David A; Krastins, Bryan; Lopez, Mary F; Karrison, Theodore; Yeo, Kiang-Teck J
Abstract: Background: We compared the rates of intraoperative parathyroid hormone (PTH) decline using the Siemens Immulite ® Turbo PTH and Roche Elecsys ® short turnaround time PTH assays in 95 consecutive surgical patients to investigate analytical and turnaround time (TAT) differences between the tests performed in the operating room (OR) vs the central clinical chemistry laboratory (CCL). Methods: Serial blood samples from 95 patients undergoing parathyroidectomy were collected and measured using the 2 immunoassays. Specimens from the first 15 patients were measured simultaneously in the OR and CCL and used for the TAT study. In addition to 2 baseline samples, specimens were collected at 5, 10, and 15 min (for some patients, >15 min) after parathyroidectomy. Results: In the TAT study, a significant difference was observed (OR median 20 min vs CCL median 27 min; P < 0.05). Of the 95 patient series, slower rates of parathyroid hormone decrease were observed in approximately 20% of the patients when comparing the Roche with the Immulite immunoassay. Conclusions: There was a slightly longer TAT in the CCL compared with running the assay directly within the OR (median difference of approximately 7 min). For a majority of the patients, both methods showed equivalent rates of PTH decline; however, for approximately 20% of the patients, there was a slower rate of PTH decline using the Roche assay.